Practical Challenges in Hybrid Communication Ecosystems Based on ITS-G5 and LTE for CACC and GLOSA - Cimoli, Bruno; Xing, Haitao; Ho, Victor; Passchier, Igor; Kakes, Geerd; Rommel, Simon; Nijmeijer, Henk; Tafur Monroy, Idelfonso (Frontiers in Future Transportation, 2022)
In this paper we report the implementation and experimental evaluation of a proposed hybrid communication ecosystem for CCAM applications such as cooperative adaptive cruise control (CACC) and smart intersections. Three wireless technologies have been suggested for communications between vehicles and intelligent traffic lights and are evaluated in this work: ITS-G5 based on IEEE 802.11p and LTE sidelink with PC5 air interface for direct short range links, and regular mobile LTE with LTE Uu air interface for long range or indirect links. The applications used are independent of the communication channel, to enable a comparison on the application level of the different communication technologies. Field experiments were carried out with two CACC-equipped vehicles and three intelligent traffic lights in two field test locations under ideal, i.e., no-traffic, conditions and with real traffic. Experimental results related to CACC show that the best performance in terms of latency is achieved by the ITS-G5 system, while LTE PC5 and LTE Uu links show a penalty of 20 and 50 ms respectively. However, experimental results show that all three communication technologies were still able to guarantee string stable performance of the vehicle platoon. Regarding the smart intersections, an analysis based on field measurements and comparison between long- and short-range solutions is proposed; the analysis includes the impact of each channel on the applications such as speed advisory and green light prediction. The reported experimental evaluation shows the potential of current mobile technologies for CCAM use cases and highlights the way for further CCAM applications based on 5G and beyond mobile networks.